2010
DOI: 10.1177/0956797610395392
|View full text |Cite
|
Sign up to set email alerts
|

Young Children Share the Spoils After Collaboration

Abstract: Egalitarian behavior is considered to be a species-typical component of human cooperation. Human adults tend to share resources equally, even if they have the opportunity to keep a larger portion for themselves. Recent experiments have suggested that this tendency emerges fairly late in human ontogeny, not before 6 or 7 years of age. Here we show that 3-year-old children share mostly equally with a peer after they have worked together actively to obtain rewards in a collaboration task, even when those rewards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
172
4
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 220 publications
(196 citation statements)
references
References 32 publications
15
172
4
4
Order By: Relevance
“…As for the effect of the work on the distribution of resources, the results obtained corroborate those reported in other studies which have shown that the work done is fundamental in the division of resources, and it is widely used even among very young children (Hamann, Warneken, Greenberg, & Tomasello, 2011;Tomasello & Warneken, 2008;Warneken et al, 2011). However, no studies were found in the literature contrasting these effects with other modes of production of goods, especially comparing the work done and the use of means of production.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As for the effect of the work on the distribution of resources, the results obtained corroborate those reported in other studies which have shown that the work done is fundamental in the division of resources, and it is widely used even among very young children (Hamann, Warneken, Greenberg, & Tomasello, 2011;Tomasello & Warneken, 2008;Warneken et al, 2011). However, no studies were found in the literature contrasting these effects with other modes of production of goods, especially comparing the work done and the use of means of production.…”
Section: Discussionsupporting
confidence: 80%
“…More specifically, it has been demonstrated that children as young as three years of age have a tendency to share most equally the rewards resulting from a collaborative effort, even when they have the opportunity to keep everything for themselves (Warneken, Lohse, Melis, & Tomasello, 2011). On the other hand, when they are in a situation where they work individually on the same task and with the same results, this egalitarian sharing tendency is not displayed.…”
Section: Palavras-chave: Cooperação; Tomada De Decisão; Justiça Distrmentioning
confidence: 88%
“…Prior work has shown that 3-year-olds share rewards equally after collaborating on a task that is identical to the one used in our study (Hamann, Warneken, Greenberg, & Tomasello, 2011;Warneken, Lohse, Melis, & Tomasello, 2011). This suggests that children in our study likely had an expectation to receive stickers in both conditions.…”
Section: Resultsmentioning
confidence: 57%
“…And in fact, when children are allowed to reallocate advantageously distributed resources, from as young as 3 years they sometimes sacrifice their extra resources to equalize. Specifically, in the second study of Hamann, Warneken, Greenberg, and Tomasello (2011; see also Ulber, Hamann, & Tomasello, 2015;Warneken, Lohse, Melis, & Tomasello, 2011), when a pair of 3-year-olds collaborated to produce resources and one child unexpectedly received more than the other, the lucky child sacrificed to equalize nearly 80% of the time. Moreover, in a control condition where the two children produced resources independently (the study was focused on the effect of collaboration), the lucky child still sacrificed to equalize nearly 40% of the time.…”
Section: Introductionmentioning
confidence: 99%